Unraveling the Nexus: Parkinson's Disease, Alpha-synuclein, Desulfovibrio, and the Gut Microbiome - Fatima Abdul Azeez (International Journal of Cell Biology and Cellular Functions, 2024)
Parkinson's disease (PD) is now recognized as a chronic condition which is once considered a highly intricate disorder involving the central, autonomic, and enteric nervous systems. The prevailing perspective attributes the disease by the formation of Lewy bodies, primarily triggered by the misfolding of α-Synuclein, leading to the demise of dopaminergic neurons in the substantia nigra. Constipation, one of the most common non-motor symptoms in PD patients, is believed to be influenced by the composition of gut bacteria. The gastrointestinal tract acts as a significant point of entry through the vagus nerve for potentially harmful microorganisms that can initiate the pathological process of PD. The vagus nerve is proposed to play a role in transmitting signals leading to the over-expression and accumulation of α-Synuclein in the brain. In a study, it was noted that individuals with PD displayed an elevated occurrence of bacteria belonging to the Desulfovibrionaceae family. Desulfovibrio (DSV) are sulfate-reducing bacteria (SRB) that are established as commensal bacteria in the human gastrointestinal tract. Desulfovibrio releases certain metabolites that trigger the aggregation of alpha-synuclein leading to play a role in the pathogenesis of PD. The presence of DSV can lead to a decline in bacterial metabolites, which plays a crucial role in gut health and contributes to the effects observed in individuals with PD. This review consolidates current knowledge on the connection between DSV and PD, emphasizing the role of the gut environment. We address the possibilities that could be considered for reducing the α-Synuclein aggregation in this study by emphasizing Desulfovibrio.
Keywords: Cellular toxicity; Desulfovibrio; Neurodegenerative Disease; Parkinson's disease; α-Synuclein